Acupuncture for acute asthma attack in an emergency department: A descriptive observational study - Man Sze Lam; Pei Jing Tan; Sean Mun Kit Lee; Wee Yee Lee (Proceedings of Singapore Healthcare, 2026)
Introduction This prospective observational study evaluated outcomes among patients receiving standard management alone compared with those receiving standard management with adjunct acupuncture for moderate acute asthma in the Short Stay Unit (SSU) of the Emergency Department (ED). The primary objective was to compare SSU-to-inpatient admission rates between the two groups. Methods We conducted a comparative observational study in the SSU of the ED at Changi General Hospital (CGH), Singapore between May 2019 and February 2020. Patients presenting with moderate asthma exacerbations were classified into two exposure groups according to whether they received acupuncture during their SSU stay. The Control Group received standard management while the Acupuncture Group received acupuncture in addition to standard care when licensed TCM physicians were available on-site. The primary outcome was SSU-to-inpatient admission rates. Peak expiratory flow rate (PEFR) before and after acupuncture treatment was evaluated as a secondary outcome. Results The Acupuncture Group demonstrated a lower SSU-to-inpatient admission rate compared with the Control Group (42.9% vs 83.3%), although the difference did not reach statistical significance (odds ratio 0.15, 95% CI 0.00–2.97, p = 0.135). Among participants who received acupuncture, PEFR improved significantly following treatment. Conclusion In this small observational study, adjunct acupuncture was associated with a lower inpatient admission rate and immediate improvement in PEFR. Although limited by small sample size and non-randomised design, these findings provide preliminary real-world evidence supporting further investigation of acupuncture in acute asthma care.